Reproducing situationally triggered urgency incontinence in a controlled environment. Issue 8 (25th September 2020) - Clarkson, Becky D.; O′Connell, Kathleen; Conklin, Cynthia A.
Abstract: Introduction: Patients with lower urinary tract symptoms often report urgency and incontinence episodes which are triggered by environmental scenarios, for example, "latch‐key incontinence." To better understand the extent of this phenomenon, and how best to reduce its impact, we tested ways to recreate these situational cues in a controlled environment and obtain cue reactivity measures. Methods: We developed a standardized set of urgency cue scenarios from interviews with sufferers of situational urgency urinary incontinence (UUI), personalized urgency, and safe cue sets consisting of photographs of specific locations, and measurements of cue reactivity during computer‐based presentation and urodynamic monitoring. Results: Common urgency and safe cues were identified for the standardized cue set. Exposure to these standardized cues elicited change in bladder sensation in 7 of 12 participants. Participants created personalized cue sets with photographs depicting their own urgency triggering scenarios; exposure to personalized cue photos elicited change in sensation in 11 of 12 participants. In addition, personalized cues elicited measurable detrusor overactivity and leakage during urodynamic monitoring. Safe cues reduced bladder sensation in five participants. Conclusion: We developed a computer‐based means of displaying cue photos which elicited cue reactivity from women suffering from situational urgency incontinence. Cue reactivity was increased by personalizing photos of cue scenarios and obtaining physiological measures from urodynamics. We have developed an appropriate way to test cue reactivity in women with situational UUI.